2015
DOI: 10.1890/es14-00488.1
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of logging roads in the Congo Basin: How persistent are the scars in forest cover?

Abstract: Abstract. Logging roads in the Congo Basin are often associated with forest degradation through fragmentation and access for other land uses. However, in concessions managed for timber production, secondary roads are usually closed after exploitation and are expected to disappear subsequently. Little is known about the effectiveness of this prescription and the factors affecting vegetation recovery rate on abandoned logging roads. In a novel approach we assessed logging roads as temporary elements in the fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…The network of logging roads in the study area [30,31] is used as a proxy of human accessibility to the forest and related risk of human induced fire outbreak. In concessions managed for timber production, secondary roads are usually closed after exploitation and a rapid regrowth of vegetation is observed after abandonment.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The network of logging roads in the study area [30,31] is used as a proxy of human accessibility to the forest and related risk of human induced fire outbreak. In concessions managed for timber production, secondary roads are usually closed after exploitation and a rapid regrowth of vegetation is observed after abandonment.…”
Section: Study Areamentioning
confidence: 99%
“…In concessions managed for timber production, secondary roads are usually closed after exploitation and a rapid regrowth of vegetation is observed after abandonment. Kleinschroth et al, [30] observed a median persistence of four years for open roads before reverting to a vegetated state and 20 years before complete disappearance (no longer distinguishable from the surrounding forest).…”
Section: Study Areamentioning
confidence: 99%
“…In the Congo Basin alone, the Ouesso-Bangui-N'Djamena, Libreville-Lomie, Cameroon-Chad, and Northern Upgrade Corridors will span parts of Cameroon, Gabon, Republic of Congo, Democratic Republic of Congo, and Central African Republic (Laurance et al, 2015a). At present, many forests in these nations are still remote and only partially accessible via logging roads and existing timber concessions (Laporte et al, 2007;Kleinschroth et al, 2015). Unless environmental safeguards are rapidly implemented, the spate of new infrastructure projects will open up large tracts of Central Africa to further pressures, such as mining, hunting, logging, and deforestation for agriculture (Laurance et al, 2006(Laurance et al, , 2015aBlake et al, 2007;Poulsen et al, 2009).…”
Section: Tip Of the Icebergmentioning
confidence: 99%
“…These projects include a large number of industrial mining projects ; over 53,000 km of proposed "development corridors" (see some examples in Figure 1) that would crisscross much of the continent (Weng et al, 2013;Laurance et al, 2015a); the world's largest hydropower-dam complex, at Inga Falls on the Congo River; ambitious plans to increase industrial and smallholder agriculture (African Agricultural Development Company Ltd., 2013;Laurance et al, 2014a,b); widespread industrial logging (Laporte et al, 2007;Kleinschroth et al, 2015Kleinschroth et al, , 2016a; and a variety of other mining ventures and energy infrastructure with accompanying roads.…”
Section: Introductionmentioning
confidence: 99%
“…On Landsat images, they are detectable with bare soil for an average of 4 years and covered with vegetation for 20 years before they are no longer distinguishable from surrounding forest (Kleinschroth et al . ). Only 12% of roads in forest concessions observed over the last 15 years have been permanently open (Kleinschroth, Healey & Gourlet‐Fleury ).…”
Section: Introductionmentioning
confidence: 97%